Preparation of products rich in resistant starch from maize starch by an enzymatic method - Zhang, Huanxin; Jin, Zhengyu (Carbohydrate polymers, 2011)
► A new way to prepare resistant starch was developed. ► The yield of resistant starch by the method is high. ► The reaction conditions were optimized. We prepared resistant starch (RS) from maize starch using a method combining α-amylase and pullulanase. We optimized reaction conditions for α-amylase, including temperature (T), pH, reaction time (t), and amount of α-amylase. The highest formation of RS (58.87%) was obtained under the following conditions: temperature, 90°C; pH, 5.5; time, 15min; and amount of α-amylase, 4μ/g. Scanning electron microscopy and differential scanning calorimetric analyses showed that maize starch underwent pasting treatment with α-amylase contained shorter amylase chains, and decreased steric hindrance among molecules compared with native maize starch. It is advantageous for amylopectin to be debranched by pullulanase, and the short amylose chains released from amylopectin can form double helices. Compared with native maize starch, maize RS showed increased crystallinity, and a larger, more compact laminiplantation structure. The increased density of the crystals greatly increases their resistance to starch-degrading enzymes. This is a promising method for preparing RS-rich products.